PENGARUH KARAKTERISTIK KOMITE AUDIT, PREDIKSI KEBANGKRUTAN DAN KEPEMILIKAN PUBLIK TERHADAP AUDIT REPORT LAG - Inneke Kusuma Ratnasari; Yanti Ardiati (Modus, 2016)
Submission of Annual Financial Statements in Indonesia organized by theFinancial Services Authority (Otoritas Jasa Keuangan/OJK). All of the Company thatthe shares are traded on the Indonesia Stock Exchange (IDX) shall submit the AnnualFinancial Report. The Indonesian Capital Market Supervisory Agency Rule (2003), listedcompanies are required to submit the audited annual financial statement to BAPEPAMand Indonesian Stock Exchange (IDX) at the latest at the end of the third month after thedate of the statement.This research was conducted in order to test the effect of the characteristics of theaudit committees, predictions of bankruptcy and public ownership lag effect on the auditreport. The study was conducted at the manufacturing companies listed in Indonesia StockExchange in 2010-2014.The results showed that the characteristics of the audit committee and bankruptcyprediction have effect on audit report lag but public ownership has no effect on audit reportlag.Keywords: audit committees characteristics, audit report lag, bankruptcy prediction,manufacturing companies, public ownership.